Didakhe: Pengajaran Kedua Belas Rasul Sebuah Pengantar - F.X. Didik Bagiyowinadi (Jurnal Orientasi Baru, 2011)
Didache is not a canonical book, but it is one of the classical literatures of theearly Church. From this book, we can explore the morality dan liturgical praxisof the early Church. This study will attempt to represent the content of Didachethat give many details of The Two Way, the way of life and the way of death,as the prebaptismal catecheses and how the community of Didache practice thebaptismal rites and Eucharist prayer. This study will search also the relationbetween Didache and the gospel of Matthew and whether both of them are fromthe same community. We can find that the community of Didache and Mattheware from the same Jewish Christian background, but they are different whenapply the Moses Law in their daily Christian life.